catena-Poly[[penta-μ-benzoato-μ-chlorido-dioxanedineodymium(III)] dioxane 2.5-solvate] - Bertke, Jeffrey A. (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, [Nd(2)(C(6)H(5)COO)(5)Cl(C(4)H(8)O(2))]·2.5C(4)H(8)O(2), consists of two Nd(III) ions bridged by one Cl(−) ion, five benzoate ions and one coordinating 1,4-dioxane molecule. One Nd(III) ion is nine-coordinate, with a very distorted monocapped square-antiprismatic geometry. It is coordinated by two chelating carboxylate groups, three monodentate carboxylate groups, one chloride ion and one dioxane molecule. A second independent Nd(III) ion is eight-coordinated in a distorted square-antiprismatic geometry by one chelating carboxylate group, five monodentate carboxylate groups and one chloride ion. The chains of the extended structure are parallel to the crystallographic b axis. There is a small amount of void space which is filled with five disordered dioxane solvent molecules per unit cell. The intensity contribution of the disordered solvent molecules was removed by applying the SQUEEZE procedure in PLATON [Spek (2009). Acta Cryst. D65, 148–155].